Ramas, familles, réseaux. Les supports sociaux de la diffusion de la santería cubaine (Cuba-Mexique) - Kali Argyriadis (Journal de la Société des Américanistes)
Ramas, families, networks. The social basis of the diffusion of Cuban santería (Cuba-Mexico). Cuban santería is following a global trend towards transnationalisation, like all of the other so-called Afro-American religions, currently found in West Africa, Europe and across the American continent. In order to grasp the full range of our topic, an analysis in terms of networks seems, at first glance, the best option. Detailed ethnography of the relationships between social actors reveals a complex ramification of individuals and groups connected by one or several intermediary links. However, such an abstract concept as « transnational network » is far from being fully satisfactory. Several contingent realities lurk behind this generic phrase, which we will attempt to refine and test by examining the situation in La Havana and the diffusion of santería in Mexico.